1995
DOI: 10.1111/j.1469-8137.1995.tb03035.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant‐parasitic nematodes and soil‐borne fungi in the decline of Ammophila arenaria (L.) Link

Abstract: In coastal foredunes, Ammophila arenaria (L.) Link grows vigorously when it is buried regularly by windblown sand and degenerates at stabilized sites. Nematodes and soil-borne fungi were found to be involved in its decline. In order to establish their role in the disease complex, seedlings of ^. arenaria were inoculated with several groups of potentially harmful soil organisms that were isolated from its root zone. Inoculation of single species of fungi did not reduce the growth of the seedlings, but combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 22 publications
2
70
0
1
Order By: Relevance
“…Evidence for selective stimulation comes from plant-soil feedback studies (Bever et al, 1997), although these studies provide net effects of the whole soil community, including symbionts and decomposers (Reinhart and Callaway, 2006). However, selective isolation and inoculation of pathogenic soil microbes has provided evidence for a number of case studies that the root zones of wild plant species indeed contain pathogenic soil microbes (De Rooij- Van der Goes, 1995;Mills and Bever, 1998;Packer and Clay, 2000;Kardol et al, 2007) and that these may be host specific . Evidence for the release of invasive plants from soil pathogens would require combined tests in the native and non-native ranges.…”
Section: Invasive Plants and Soil Microbial Parasites And Pathogensmentioning
confidence: 99%
“…Evidence for selective stimulation comes from plant-soil feedback studies (Bever et al, 1997), although these studies provide net effects of the whole soil community, including symbionts and decomposers (Reinhart and Callaway, 2006). However, selective isolation and inoculation of pathogenic soil microbes has provided evidence for a number of case studies that the root zones of wild plant species indeed contain pathogenic soil microbes (De Rooij- Van der Goes, 1995;Mills and Bever, 1998;Packer and Clay, 2000;Kardol et al, 2007) and that these may be host specific . Evidence for the release of invasive plants from soil pathogens would require combined tests in the native and non-native ranges.…”
Section: Invasive Plants and Soil Microbial Parasites And Pathogensmentioning
confidence: 99%
“…Such additive, synergistic, and antagonistic effects have been observed aboveground, as well as belowground. For example, in papaya (Carica papaya) and hoary cress (Lepidium draba), exposing plant individuals to two or more aboveground herbivore species resulted in additive effects (Fournier et al 2006, Puliafico et al 2008, whereas exposing the foredune grass Ammophila arena-ria to a number of pathogenic soil fungi and rootfeeding nematodes resulted in synergistic growth reduction effects (De Rooij-van der Goes 1995). The interaction effects of plant enemies may depend on the number of interacting enemy species: effects of rootfeeding nematode species on A. arenaria were additive when exposing plants to two species (Brinkman et al 2008), but antagonistic when testing effects of three nematode species (Brinkman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This plant species is very tolerant to sand burial and promotes dune formation by accumulating wind-blown sand. Ammophila arenaria also develops extensive root systems which are colonized by both mutualistic and parasitic organisms [8,21,29]. Several previous studies have shown the presence of AMF associated with A. arenaria [13,14,21,23].…”
Section: Introductionmentioning
confidence: 99%